A model of X-Ray emitter emission characteristics measuring - Malakhova, Maryna; Reva, Sergiy; Styervoyedov, Mykola (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2017)
A model for measuring of the X-ray emitter individual emission characteristics for computerized X-ray control system has been created. The strategy of empirical data generation for calculating the coefficients of the transformation function of the typical emission characteristics to individual ones in order to improve the accuracy of the results has been defined. An accuracy estimation of the results has been performed.